Brief Review of Q CAD Used in Mathematics: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
QCAD is a 2D design and drawing computer-aided design (CAD) software tool. It is available for Linux,Apple macOS,Unix and Microsoft windows. The QCAD user interface is built on the Qt framework.This paper presents the results of a comparative review of several groups of open - source software(0SS) for modeling analysis of constructions. Software products of two categories are considered.1)Geometricallygraphically modelingdrawing of the structures- 2D, 3D CAD.2)Calculation and analysis of building structures under different load conditions and geometry including geotechnical problems.3)Drawing Methods in QCAD Cartesian Coordinate System Useful drawings and objects. Draw Objects Drawing Methods.